1, 1′-Ferrocenedicarboxylic acid/tetrahydrofuran induced precipitation of calcium carbonate with a multi-level structure in water. Issue 41 (15th October 2021) - Zhou, Lihong; Wang, Guanghui; Du, Jie; Zhao, Qinjiang; Pei, Xiang
Abstract : Multi-molecules co-regulate the orderly morphology and structure of CaCO3 precipitates and the influence of ether bonds on the formation of CaCO3 precipitates. Abstract : A system of organic solvents and ligands had been successfully applied to regulate the coordination of metal ions in organic chemistry. Inspired by previous work, we conducted a study on the effect of 1, 1′-ferrocenedicarboxylic acid (FA)/tetrahydrofuran (THF, aprotic solvent) on the precipitation of calcium carbonate (CaCO3 ). The influence of FA concentrations was systematically investigated to achieve controllable and reliable CaCO3 particles. As a control, the effect of H2 O–THF solutions on CaCO3 precipitation was explored and compared with that of H2 O-1, 4-dioxane solutions. It was demonstrated that the presence of FA/THF in water solutions not only affected the dimensions and morphology of the precipitates but also determined the CaCO3 polymorphism. The proportion of THF in the solvent affects the polymorphism distribution of CaCO3 . The presence of THF led to the formation of rod-like CaCO3, and the higher the proportion of THF in the solvent, the smaller the size of CaCO3 particles found. This was a common feature of ether solvents, and identical results could be obtained with 1, 4-dioxane under the same experimental conditions. FA was the driving force for the formation of calcite, which could stack CaCO3 layers on the surface of CaCO3 particles induced by THF. The product exhibited a multi-level structure. The results shed light on the mechanism of FA and ether solutions during precipitation of CaCO3 and opened a novel synthetic avenue of regulating CaCO3 precipitation with a multi-level structure.